Health behaviors and health status of Korean middle-aged men by marital status: Korea Community Health Study, 2015 - Yongho Jee; Youngtae Cho (Epidemiology and Health, 2019)
OBJECTIVES Previous studies have shown that marital status is associated with household composition and living arrangements, which partially explain observed differences in health status according to marital status. However, due to the rapid socioeconomic and demographic transformations of the last few decades, the distribution of marital status among middle-aged adults has become more diverse. Therefore, this study aimed to obtain up-to-date information on the associations between marital status and health and to investigate the implications of these findings for conventional explanations of the health effects of marriage. METHODS The data for this study were obtained from the 2015 Korean Community Health Study. We compared 4 modifiable lifestyle behaviors—smoking, alcohol consumption, physical activity, and self-rated health status—as outcome variables in association with marital status in Korean middle-aged men (age 40-44) living in Seoul and other regions. RESULTS Married men showed the lowest cigarette smoking prevalence and the highest subjective health status both before and after adjusting for education and income. The odds of engaging in vigorous physical activity did not show a major difference before and after adjustment for income and education. CONCLUSIONS In married men, the prevalence of cigarette smoking was lowest and subjective health status was highest, similar to previous studies. However, the prevalence of engaging in physical activity was highest in divorced/widowed/separated men. The health behaviors and health status of Korean middle-aged adults should be more closely followed, since they are representative of demographic changes in the Korean population.